Evaluation of Scheduling Schemes for Ecological Water Supplement of Rivers in Guangdong-Hong Kong-Macao Greater Bay Area Based on MIKE 11 - GAO Huayong; ZHAO Bikui; GUO Xiaojuan; TAN Chao (Renmin Zhujiang)
To achieve joint scheduling of the ecological water supplement project and the estuarine sluice of the cross-boundary Yachong River in the Guangdong-Hong Kong-Macao Greater Bay Area, the mathematical model of hydrodynamics and water quality of the one-dimensional river network based on MIKE 11 was constructed by considering the significant jacking role of the open sea tide level. In addition, different types of scheduling schemes were designed, including natural state scheme, current state scheme, and joint scheduling scheme, so as to evaluate the effect of each scheme in reducing pollutant concentration and improving water quality. The results show that in the daily water supplement scheduling, if the estuarine sluice and ecological water supplement are not jointly scheduled, the water renewal efficiency of the Yachong River is low, and if they are jointly scheduled, the water quality is better improved when water is supplied for two hours per day in the first five days of the dry season, along with a lower electricity cost and the best comprehensive evaluation index. In the flood season with flood control and drainage scheduling, there is no need for ecological water supplement scheduling. In addition, the water quantity analysis shows that the comprehensive evaluation index of different water supplement schemes is opposite to the response law of the inflow water volume and outflow water volume and their ratio of typical sections. The evaluation results can provide a scientific basis for the water environment and quality improvement schemes of the Yachong River.